Disorders of the Hand Volume 3: Inflammation, Arthritis and Contractures - Trail, Ian A.; Trail, Ian A.; Fleming, Andrew N.M.; Fleming, Andrew N.M. (Springer London : Imprint: Springer, 2015)
This book comes at a time when significant advances in the understanding of hand disorders have resulted in vast improvements in the quality of life for patients. It describes the techniques and practices for the diagnosis and treatment of various disorders of the hand and wrist. Each condition is discussed in detail and illustrated with images, radiographs and line drawings. Clinical pearls are provided for every chapter to provide practical guidance on surgical procedures.   Disorders of the Hand contains contributions from many of the hand surgeons who are at the forefront of this evolving area in the management of both elective and trauma hand surgery. This volume and its three sister volumes aim to improve care for current patients with hand and wrist complaints, while inspiring surgeons to think in greater detail about treatment options that will provide even better care in the future.